(untitled) (Journal of Pharmaceutical Negative Results, 2021)
The visual evoked potential is an electrophysiological study used to assess the visual pathway to detect the occipital response to a light stimulus. The aim of the study is: early diagnosis of diabetic retinopathy by VEP study in patients who were newly diagnosed with diabetes mellitus (DM), with assessment of visual pathway impairment due to diabetic retinopathy. Methods: This study was conducted as a case-control study that was carried out on ninety (90) patients presented with a new diagnosis of type II diabetes mellitus (within 3 years from the time of diagnosis) who attended the medical departments of Alazher University Hospital during the period from December 2020 to the end of October 2021, and twenty healthy persons of the same age and sex were used as a control group. Each participant has undergone a battery of neurological and ophthalmological tests, including visual-evoked potentials. The patients have received reverse-patterned VEP through a single eye. Results: There were statistically significant differences in latency of N 75 and P 100 and amplitude of N 75 to P 100 between patients and the control group. Also, there was a statistically significant difference in latency between P 100 and N 75. There was no significant difference between the results of VEP and the age of patients, sex, or in between both sides of the eye. Conclusions: This study diagnoses diabetic retinopathy early and analyzes its prognosis by observing changes in VEP pathway latency and P100 wave amplitude in group A patients.